ANALISIS RENCANA PELAKSANAAN PEMBELAJARAN (RPP) BIOLOGI BERKARAKTER KELAS XI SMA NEGERI UNTUK STANDARISASI RPP DI KOTA SOLOK - Aprianti, Elirta Dewi; Mulyati, Mulyati; Nerita, S.Pd, M.Pd, Siska (Pendidikan Biologi, 2014)
ABSTRACT Education is a conscious and deliberate effort to create an atmosphere of learning and the learning process so that learners can actively develop her potential. To achieve that all teachers ar e expected to design a lesson plan (RPP) in accordance with the standards of Teacher Performance Assessment Instrument (IPKG). In this case the teachers of biology in the city of Solok generally there are those who do not understand the reference in designing and making lesson plans. In designing the lesson plan there are teachers who take reference from the internet and copying existing RPP without looking at the characteristics of the material that students will be taught appropriate or not so as a result of the learning process is not maximized. The purpose of this study is to investigate the standardization of Lesson Plan (RPP) in SMA Solok. This research is a descriptive study, the sampling technique is the total sampling by collecting RPP State high sc hool biology  teacher  in  Solok  and  analyze  lesson  plans  based  on  a  questionnaire  that  has  been developed by Mulyati ,et al (2013). From this study showed that in terms of the completeness of components obtained an average RPP for completeness existing RPP component is 66.75% and33.25% no. Based on the analysis results, we can conclude that the RPP in Solok Standard Self categorized by the percentage of 68.89%